2017
DOI: 10.1155/2017/7920438
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Deep Regional Blocks toward Deep Nerve Hydrodissection in the Upper Body and Torso: Method Description and Results from a Retrospective Chart Review of the Analgesic Effect of 5% Dextrose Water as the Primary Hydrodissection Injectate to Enhance Safety

Abstract: Deep nerve hydrodissection uses fluid injection under pressure to purposely separate nerves from areas of suspected fascial compression, which are increasingly viewed as potential perpetuating factors in recalcitrant neuropathic pain/complex regional pain. The usage of 5% dextrose water (D5W) as a primary injectate for hydrodissection, with or without low dose anesthetic, could limit anesthetic-related toxicity. An analgesic effect of 5% dextrose water (D5W) upon perineural injection in patients with chronic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 50 publications
2
65
0
1
Order By: Relevance
“…38,39 Similar effects have been reported in a retrospective analysis of the results from regional hydrodissection using dextrose in patients with various neurogenic pain conditions of the upper body. 40 Several neural mechanisms have been hypothesized. First, downregulation of the transient receptor potential vanilloid receptor 1 ion channel is a primary therapeutic target in chronic pain management.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Similar effects have been reported in a retrospective analysis of the results from regional hydrodissection using dextrose in patients with various neurogenic pain conditions of the upper body. 40 Several neural mechanisms have been hypothesized. First, downregulation of the transient receptor potential vanilloid receptor 1 ion channel is a primary therapeutic target in chronic pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of 5% dextrose into the caudal epidural space has been demonstrated by Smigel et al to result in prompt and consistent multi-segmental post-injection analgesia and a cumulative analgesic effect in patients with chronic low back pain with radiation to buttock or leg [25]. In a retrospective data collection of consecutive patients with severe neuropathic pain, Lam et al demonstrated both the safety and efficacy of 5% dextrose solution without the use of lidocaine to treat neuropathic pain caused by nerve roots or plexi in consecutive patients [9]. This is of particular interest as in the absence of lidocaine, optimal HD volumes can be utilized without the concern for lidocaine toxicity.…”
Section: Injectate For Hdmentioning
confidence: 98%
“…Other clinical studies have also used this technique to treat neuropathic pain related to deep nervous structures or neuro-axial spine [9]. There are currently no reviews available which summarize the key literature on this technique and its use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…nerve ischemic damage, by injecting D5W to detach the entrapped nerves from the surrounding tissue. 5,6 Here, we reported a patient with chronic MP, who successfully recovered after a series of ultrasoundguided nerve hydrodissection with D5W. A 35-year-old woman presented with decreased sensation and intermittent shooting pain on the anterolateral aspect of the right thigh for 20 years.…”
mentioning
confidence: 98%
“…7 Although the mechanism of dextrose on the nerve is not fully understood, the following hypothesis has been reported: D5W may reduce neurogenic inflammation by blocking transient receptor potential vanilloid receptor-1, which initiates the inflammatory cascade on the peripheral nerve. 5 In addition to the pharmacologic effect of D5W, nerve hydrodissection might have contributed to the therapeutic effect by creating space to release the pressure and adhesions on the entrapped nerve, reversing ischemic damage and improving nerve conduction. 6 Hence, we suggest that hydrodissection with D5W may be used as an alternative intervention to enhance the recovery of MP, even in extremely chronic cases.…”
mentioning
confidence: 99%